Outer Retinal Oxygen Consumption of Rat by Phosphorescence Lifetime Imaging - Wanek, Justin; Blair, Norman P.; Shahidi, Mahnaz (Current eye research, 2012)
Purpose: Since the metabolic function of the retinal tissue is altered due to physiologic changes or disease, measurements of outer retinal oxygen consumption (QOR) may be beneficial in assessment of retinal status. The purpose of this study was to report measurements of QOR in rats using a phosphorescence lifetime imaging technique. Methods: Phosphorescence lifetime imaging was performed and retinal PO2 maps were generated in 10 rats under a light-adapted condition. Depth-resolved retinal PO2 profiles were derived from the PO2 maps. From the profiles, the maximum outer retina PO2 (PmaxO2) was obtained and QOR was calculated using a one-dimensional oxygen diffusion model. Repeatability, inter-location variability, and inter-subject variability of PmaxO2 and QOR measurements were established. Results: Intraclass correlation coefficients of repeated measurements of PmaxO2 and QOR were 0.89 and 0.70, respectively (P < 0.001). Inter-location variability of PmaxO2 and QOR measurements at superior to inferior contiguous locations on the retina were on average 9 mmHg and 0.22 ml O2/100 g-tissue-min, respectively. Mean and standard deviation of PmaxO2 and QOR measurements averaged over all rats were 60 ± 16 mmHg and 0.73 ± 0.28 ml O2/100 g-tissue-min, respectively. Inter-subject variability of PmaxO2 and QOR measurements was on average 2.3 and 1.5 times inter-location variability, respectively. Conclusions: Measurements of outer retinal oxygen consumption can be made by phosphorescence lifetime imaging and may be of potential value for detecting changes in retinal oxygen metabolic activity due to altered physiological and pathological conditions over multiple locations and time points.